in vitro Screening of N-Naphthylhydroxamic Acids as DNA Binding Agents - Pardhi, Manish; Verma, Bharati; Thakur, Yamini; Khilari, Rubi; Tripathi, Mamta; Pande, Rama (Asian Journal of Chemistry, 2016)
The in vitro interaction between N-1-napthylcaprohydroxamic acid and N-1-napthyllaurohydroxamic acid and ct-DNA was investigated in physiological buffer (7.4 pH) by UV-visible, fluorescence spectroscopy as well as viscosity measurement. The result indicated that both the hydroxamic acid bind to ct-DNA. The binding constant of N-1-naphthylcaprohydroxamic acid and N-1-naphthyllaurohydroxamic acid was found to be respectively 4.1 × 102 L mol-1 and 3.4 × 104 L mol-1. The binding constant, number of binding sites and quantum yield were calculated by fluorescence quenching method. Competitive studies with ethidium bromide have shown that the N-1-naphthyllaurohydroxamic acid can displace the ct-DNA–bound ethidium bromide suggesting strong competition with ethidium bromide. The negative value of thermodynamic parameters (DG, DH, DS) and positive value of cell potential (E) showed the spontaneity of the reaction. Binding of hydroxamic acids to ct-DNA was driven mainly by hydrophobic interaction and van der Waals force of attraction. Viscometric studies complimented the spectroscopic studies results, where a small linear increase in the relative viscosity of the ct-DNA solution was observed. The molecular docking was also used to predict the mode of binding of the hydroxamic acids with ct-DNA Conclusively, both hydroxamic acids are found to be strong ct-DNA binders and the modes of binding were intercalative and groove binding for N-1-naphthyllaurohydroxamic acid, N-1-naphthylcaprohydroxamic acid respectively.